Analysis of School Culture Implementation in Forming Students’ Religious Character - Elce Purwandari; Hadiwinarto Hadiwinarto; Zuhri Zuhri; Nurus Amzana; Sriyanti Sriyanti (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of education is essential to form a complete human being, especially as a divine-human being. This study aims to determine the habits of students in the formation of their religious character. The method used in this research is quantitative in the form of a survey. The data collection technique was carried out using an online questionnaire in the form of a Google Form which was analyzed quantitatively descriptively. Sources of data are students of grade 3 Madrasah Ibtidaiyah (MI) State Preparation (PN) Rupit, Musi Rawas Utara as many as 25 students. The results of the study revealed that the application of school culture was emphasized on Islamic culture and its religious character was instilled through school culture, some children had implemented their religious culture at school such as reading the Koran, maintaining cleanliness, praying before and after studying, respect for teachers, and tolerance. This research is unique because it has never been done before at MI PN Rupit. The contribution of research can provide understanding for other schools that want to implement a school culture based on religious character, provide references for other researchers who want to conduct research related to the religious character of students formed through school culture.